Disambiguating Babylon - Komen, Erwin R. (The Bible translator, 2018)
Translating the name “Babylon” in some languages requires that a choice be made whether the name refers to a city, a nation, or a country. This article discusses how the meaning can be determined on the basis of the immediate context, the larger context, the occurrence of collocations, and by logical inferences. It discusses the additional problems related to places where “Babylon” is personified and where it is used metonymically. An appendix contains a list of suggested choices. The procedures provided here can be applied to similar disambiguation problems for other names, such as Judah and Israel.